Effect of Medium Quenching and Temperature on Corrosion Behavior of Aluminum Alloy 6061 - Kassouha, Abbad; Entakly, Sami (Al-Nahrain Journal for Engineering Sciences, 2017)
In the present work the effect of heat treatment processes at different temperatures and in different quenching media on mechanical properties in addition to corrosion behavior in different pH solutions of aluminum alloy 6061 was achieved.The alloy was received as fabricated and the solution heat treatment processes was achieved at temperatures (490,530,570 °C), then quenching for every degree was done in two media (water, oil) to obtain on six samples. The artificial aging was done on every sample at temperature (160°C) for one hour.The microstructure was examined to show Mg2Si in every sample.The results of hardness test showed that the hardness of alloy increased with increasing heat treatment temperatures, and at the same temperature the quenched specimens in oil had higher hardness.On the other hand, the tension tests showed that the strength of alloy increased with increasing of heat treatment temperature, and at the same temperature the quenched specimens in water had higher hardness.The results of corrosions test showed that the heat treatment operations improved corrosion resistance, and the lower value was get upon treating at 530°C.